Farrowing interval in crossbred sows treated with hormones during peripartum period - SNEH,; SINHA, A K; SINGH, BALRAJ; SINGH, S K (The Indian Journal of Animal Reproduction, 2023)
Crossbred sows of Tamworth X Desi breed were treated with PGF2a and/ or oxytocin either on day111 of gestation or after the birth of first piglet. Weaning was performed either on day 48 or 56 and thesows were mated during the first and subsequent estrus postweaning. Farrowing interval was significantlyshorter in all the treabnent groups as compared to control. The interval was apparently shorter in thegroup of sows where weaning was practiced on day 48 as compared to 56.
Keywords: Farrowing interval, peripartum period; sows; PGF2alpha; oxytocin